1982
DOI: 10.1159/000182436
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Effect of Saline Loading on Glycerol-Induced Acute Renal Failure

Abstract: To determine whether saline loading actually protects against acute renal failure, both Gn and BUN were measured in rats drinking either tap water or 1% saline for 1–3 months. At 24 and 48 h after an injection of 10 ml/kg i.m. of 50% glycerol in water, Gn was equally reduced in saline-drinking and water-drinking rats as compared to uninjected rats. The daily intraperitoneal injection of saline for 1–3 months also was not protective. At 48 hours after glycerol injection, the BUN concentration in saline-drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…0 animals pretreated with equimolar saline. We performed an additional control with hypertonic saline since some but not all studies have suggested that hypertonic saline may be beneficial in this model of acute renal injury (31,32). Basal GFR in the three groups was not different.…”
Section: Effect Of Pyruvate On Renal Function and Structure In Glycermentioning
confidence: 99%
“…0 animals pretreated with equimolar saline. We performed an additional control with hypertonic saline since some but not all studies have suggested that hypertonic saline may be beneficial in this model of acute renal injury (31,32). Basal GFR in the three groups was not different.…”
Section: Effect Of Pyruvate On Renal Function and Structure In Glycermentioning
confidence: 99%
“…In the case of acute renal failure, or acute tubular necrosis, two maneuvers have been espe cially effective in reducing the frequency and severity of the acute azotemia: the first is the protection conferred by the ingestion of sodium chloride [1][2][3][4], the second is protection conferred by prior acute renal failure [5][6][7][8][9], Recent studies indicate that the administration of sodium chloride protects against many forms of renal insult in cluding injury induced by nephrotoxins and myohemoglobinuria [10]. Cross-protection also exists between my ohemoglobinuric (induced by glycerol injection) and nephrotoxic acute renal failure, independently of which agent is administered first or second [8], Although is chemia-induced renal injury is a well-described model of acute renal failure [11,12], protection conferred by a prior, unrelated type of renal injury against a subsequent, is chemia-induced acute renal failure has not been studied.…”
Section: Introductionmentioning
confidence: 99%